Slavdom as Christendom`s colony - Slavonic identity according to Zadruga = Słowiańszczyzna jako kolonia chrystianizmu - tożsamość słowiańska według Zadrugi - Bielawski, Paweł (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The topic of this article is Slavonic identity according to the Zadruga movement. Zadrugians believed that normal cultural and civilizational development of a nation is possible only if there is harmony between the ethnos and spirituality. The believed that Christianity not only alienated Slavs from their native culture and spirituality but also subjugated them to the (German) Holy Roman Empire and Papacy - prime powers of Christendom - through symbolic power.
Keywords: Slavdom; identity; Zadruga; Christianity; słowiańszczyzna; tożsamość; chrześcijaństwo